Management Buyout Proposals and inside Information - LEE, D. SCOTT (Journal of Finance, 1992)
ABSTRACT This paper explores stock price behavior surrounding withdrawn buyout proposals to determine whether managers' proposal announcements reveal any information which is unrelated to the efficiency gains associated with completed buyouts. On average, firms whose managers withdraw buyout proposals do not sustain significantly positive stock price effects unless they receive subsequent acquisition bids. In addition, managers of firms with completed buyouts are no more likely to have access to inside information than managers who withdrew proposals. I interpret this evidence as inconsistent with the notion that inside information commonly motivates management buyout proposals.